Holocene relative sea-level histories of tropical islands - Tan, Fangyi (Nanyang Technological University, 2023)
Holocene relative sea-level (RSL) data offer important context for future sea-level changes. Predictions of the spatial patterns of RSL change to deeply uncertain, but potentially catastrophic ice-sheet melt rely on glacial isostatic adjustment (GIA) models that are calibrated to Holocene RSL data. In particular, RSL changes in tropical locations distal from the deglaciation centres of past ice sheets are sensitive to the input of meltwater into the oceans (otherwise known as ‘ice-equivalent sea-level changes’). These tropical Holocene RSL records provide key information to fine-tune the ice models assumed in GIA models. Holocene RSL data have also been used to unravel the relationships between past climates, ice sheets and sea level, offering insights into the processes and interactions driving RSL changes. However, our understanding of Holocene RSL changes is hindered by a lack of high-resolution data in tropical regions. The potential contribution of Antarctica to periods of rapid RSL rise (meltwater pulses) in the past are still debated due to the large uncertainty and temporal gaps in early- to mid-Holocene RSL data – despite Antarctica being the largest source of uncertainty in future sea-level projections.